Sp17 Protein Expression and Major Histocompatibility Class I and II Epitope Presentation in Diffuse Large B Cell Lymphoma Patients. (24th October 2017) - Ait-Tahar, Kamel; Anderson, Amanda P.; Barnardo, Martin; Collins, Graham P.; Hatton, Chris S. R.; Banham, Alison H.; Pulford, Karen
Abstract : Improved therapies are urgently needed for patients with diffuse large B cell lymphoma (DLBCL). Success using immune checkpoint inhibitors and chimeric antigen receptor T cell technology has fuelled demand for validated cancer epitopes. Immunogenic cancer testis antigens (CTAs), with their widespread expression in many tumours but highly restricted normal tissue distribution, represent attractive immunotherapeutic targets that may improve treatment options for DLBCL and other malignancies. Sperm protein 17 (Sp17), a CTA reported to be immunogenic in ovarian cancer and myeloma patients, is expressed in DLBCL. The aim of the present study was to investigate Sp17 epitope presentation via the presence of a cytotoxic T cell (CTL) and a CD4 T-helper (Th) response in DLBCL patients. A significant γ -interferon CTL response was detected in peripheral blood mononuclear cells of 13/31 DLBCL patients following short-term cell stimulation with two novel HLA-A ⁎ 0201 peptides and one previously reported HLA-A ⁎ 0101-restricted nine-mer Sp17 peptide. No significant responses were detected in the HLA-A ⁎ 0201-negative DLBCL patients or four healthy subjects. A novel immunogenic 20-mer CD4 Th Sp17 peptide was detected in 8/17 DLBCL patients. This is the first report of a CTL and a CD4 Th response to Sp17 in DLBCL and supports Sp17 as a potential immunotherapeutic target for DLBCL.